2019
DOI: 10.21921/jas.v6i03.16213
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lanc like G protein-coupled receptor-2with BOP and BTB/POZ in Stress Tolerance and High Yielding trait of Pigeonpea

Abstract: Pigeonpea is drought resilient crop; relatively more drought tolerant than other legume crops. Through detailed evaluation and multi-location trials of cross derivatives, we identified 65 better performing pigeonpea lines. Among these lines, high yielding and stress-tolerant accessions were identified. From our earlier MYB network and flowering genes networks, we could identify tightly linked co-expressinggenes for yield traits. Semi-quantitative expression analyses showed that the defending type drought stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Characterization and evaluation of available germplasm for different agro-morphological and biochemical traits is necessary to identify the effect of different genes on the phenotypes. We have already developed and evaluated high yielding lines in pigeon pea (Arumugam et al, 2018), identified diverse markers and validated the developed high yielding lines (Singh et al, 2020), genes and genes network were also being cracked (Chaudhary et al, 2017;Yasin et al, 2018;Yasin et al, 2019). In continuation to that, the present study was carried out with an objective to characterize two hundred selected pre-breeding accessions for the qualitative traits to estimate the genetic variability, heritability, coefficient of variation and character association analysis.…”
Section: Introductionmentioning
confidence: 98%
“…Characterization and evaluation of available germplasm for different agro-morphological and biochemical traits is necessary to identify the effect of different genes on the phenotypes. We have already developed and evaluated high yielding lines in pigeon pea (Arumugam et al, 2018), identified diverse markers and validated the developed high yielding lines (Singh et al, 2020), genes and genes network were also being cracked (Chaudhary et al, 2017;Yasin et al, 2018;Yasin et al, 2019). In continuation to that, the present study was carried out with an objective to characterize two hundred selected pre-breeding accessions for the qualitative traits to estimate the genetic variability, heritability, coefficient of variation and character association analysis.…”
Section: Introductionmentioning
confidence: 98%